The association between plasma carnitines and duration of diabetic ketoacidosis treatment in children with type 1 diabetes - Okdemir, Deniz; Acikgozoglu, Aysel; Akgun, Abdurrahman; Esen, Ihsan (Walter de Gruyter Gmbh, 2022)
Objectives The aim of this study is to determine the plasma free carnitine and acyl-carnitine levels at the time of diabetic ketoacidosis (DKA) diagnosis, and at the end of DKA treatment and to investigate their association with the duration of DKA treatment in children with DKA. Methods A total of 40 children with DKA who were treated consecutively in a tertiary health center for DKA were included in the study. The median age of the children was 11.3 years (1.1-17.5) and 25 of them (62.5%) were girls. In addition to routine blood tests, plasma free carnitine and acyl-carnitine levels were measured just before the start of intravenous insulin therapy and at the time of discontinuation of intravenous insulin therapy when DKA therapy was completed. Results There was no difference in plasma free carnitine and acyl-carnitine levels before and after DKA treatment (p=0.776 and p=0.743 respectively). However, while the frequency of low plasma free carnitine was 30% at the beginning of the treatment, it was observed that this frequency was 20% at the end of the DKA treatment. There was no correlation between duration of DKA treatment and plasma free carnitine or acyl-carnitine levels at admission (p=0.497, r=-0.111 and p=0.474, r=0.116 respectively). Conclusions There is no a relationship between duration of DKA treatment and plasma free carnitine or acyl-carnitine level at admission in children with DKA.
Keywords: acyl-carnitine; carnitine; ketoacidosis